PERANAN FILSAFAT DALAM PERKEMBANGAN LINGUISTIK - Adinda Febry (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2022)
Philosophy is a science that relates scientific thinking or can be defined as the science of thinking. The term linguistics is often expressed with various terms or names. Some are stated with linguistics, linguistic introduction, general linguistics, or general linguistic knowledge. However, with different terms, the substance of the study is the same, namely language. Linguistics is the science of language, the science that examines, analyzes or studies language in general, which includes regional languages, Indonesian languages, or foreign languages. Language as the object of linguistic study is an arbitrary system of sound symbols used by members of social groups to cooperate, communicate, and identify themselves. This article describes the role of philosophy and language. This happened before language was born. Linguistics was studied by philosophers. Philosophy, which has the highest position in the linguistic layer, is the basis and direction for the development of linguistics. The data in this article were obtained through scientific journals, research articles, and relevant books on the elements of Linguistic development in the Philosophy of Science. The results of the search and review of the literature show that the role of Philosophy in the development of Linguistics is very meaningful.